Legal Framework and Consumer Protection in Indonesia’s Digital Economy: Challenges, Gaps, and Reform Directions - Prabowo, Muchammad Shidqon (Law and Democracy Insight, 2025)
The rapid growth of Indonesia’s digital economy has transformed the way consumers interact with products and services, creating new opportunities as well as new risks. This study examines the effectiveness of the current legal framework in protecting digital consumers in Indonesia, focusing on existing laws, draft regulations, enforcement challenges, and potential improvements. The analysis finds that while Indonesia has established foundational regulations, including the Consumer Protection Law, the Personal Data Protection Act, and financial sector guidelines, these frameworks remain fragmented and sometimes outdated. Enforcement challenges, such as complex click-wrap agreements, limited consumer awareness, and frequent data breaches, further limit the protection of consumer rights. To address these issues, the study highlights the need for comprehensive regulatory reform, harmonization of existing laws, and the adoption of hybrid approaches that integrate legal oversight with technological solutions. Strengthening legal mechanisms, improving online dispute resolution, increasing the capacity of consumer protection agencies, and enhancing digital literacy are also essential measures. Comparative insights from countries like Malaysia and China demonstrate the benefits of clear regulations, strict oversight, and integrated enforcement mechanisms. Overall, the study emphasizes that effective consumer protection in Indonesia’s digital economy requires coordinated legal, institutional, and technological strategies to ensure transparency, accountability, and equitable safeguards for all consumers.